Compatibility studies on some polymer blend systems by electrical and mechanical techniques - Saad A L G; El-Sabbagh S (Journal of Applied Polymer Science, 2001)
Electrical and mechanical studies were systematically performed on natural rubber(NR) blended with different types of synthetic rubber such as styrene-butadiene rubber(SBR), polybutadiene rubber(BR), and ethylene-propylene-diene monomer (EPDM) as non-polar rubbers and nitrile-butadiene rubber(NBR) and chloroprene rubber (CR) as polar rubbers. The NR/SBR, NI/BR, NR/EPDM, NR/NBR, and NR/CR blends were prepared with different ratios (100/0, 75/25, 50/50, 25/75, and 0/100). Measurements were taken of the permitivity (E) and dielectric loss (E) of these blends over a broad range of frequencies (100 Hz-100 kHz) and at room temperature (approximately 27 degrees Celsius). The compatibility results obtained from the dielectric measurements were comparable with those obtained from the calculation of the heat of mixing. Scanning electron microscopy confirmed these results and revealed that NR/SBR and NR/BR blends were compatible while NR/EPDM, NR/NBR, and NB/CR were incompatible. To resolve the difficulty of phase seperation (incompatibility) between NR and EPDM, NBR, or CR, a third component (compatibilising agent) such as SBR or poly(vinyl chloride) (PVC) was added to these blends. The experimental data of dielectric and mechanical measurements revealed that the addition of either SBR or PVC could improve the compatibility of such blends to a certain degree.
Source Year: 2001
Keywords: Polymer blend